Measures of left atrial function predict incident atrial fibrillation in STEMI patients treated with primary percutaneous coronary intervention. (15th July 2018) - Modin, Daniel; Olsen, Flemming Javier; Pedersen, Sune; Jensen, Jan Skov; Biering-Sørensen, Tor
Abstract: Rationale: Atrial fibrillation (AF) is the most common arrhythmia following acute myocardial infarction (AMI). Maximal left atrial (LA) volume is the only echocardiographic atrial parameter employed clinically to assess risk of AF development. Objective: This study sought to determine the prognostic value of left atrial functional measures such as left atrial emptying fraction (LAEF) and left atrial expansion index (LAi) in predicting incident AF in the post-STEMI setting. Methods and results: STEMI patients treated with primary percutaneous coronary intervention (pPCI) at Gentofte Hospital, Denmark were prospectively enrolled from September 2006 to December 2008 and had an echocardiogram performed a median 2 days (interquartile-range: 1-3 days) following pPCI. LA maximal volume, LA minimal volume, LAEF and LAi were measured from echocardiograms of 373 patients using the area-length method. End point was incident AF. Median follow-up time was 5.6 years (interquartile-range: 5.0-6.1 years), 24 patients (6%) developed incident AF, and follow-up was 100%. In multivariable Cox regression, LAEF and LAi but not maximal LA volume remained independent predictors of AF. Results were similar in competing risk analysis treating all–cause mortality as a competing risk. LAEF and LAi, but not maximal LA volume, added incremental prognostic information in predicting incident AF when added to the CHARGE-AF risk score and the CHA2DS2-VASc score. Conclusion: LAEF and LAi independently predicted incident AF following STEMI and added incremental prognostic information in addition to established predictors of AF. Maximal LA volume was not an independent predictor of incident AF after multivariable adjustment. Highlights: Only measurement of maximal left atrial volume is included in current guidelines. Measures of left atrial function are superior to maximal left atrial volume. Measures of left atrial function predict atrial fibrillation after STEMI.